Wild epiphytic Bangladeshi orchids Cymbidium aloifolium (L.) Sw. and Papilionanthe teres (Roxb.) Lindl. potentially modulate the immune functions in Swiss albino mice - A. M. Abu Ahmed (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This research investigated the immunomodulatory potentials of two medicinally important wild epiphytic Bangladeshi orchids Cymbidium aloifolium and Papilionanthe teres using Swiss albino mice. Materials and Methods: Orchid extracts were prepared using a cold methanol extraction proce¬dure. To assess the immunomodulatory action, Swiss albino mice of either sex weighing 2535 gm were divided into five groups each with six animals. Sheep red blood cells (SRBC) of 0.5 × 109 cells/ml were used to immunize all mice on the 7th day, and a booster dose of the same quan¬tity of SRBC was given on the 11th day of the experiment. After 14 days of oral treatment with 100 and 200 mg/kg bw of orchid extract, the mice were sacrificed to collect serum and organs. Hematological assays, delayed type of hypersensitivity assays, phagocytic index (PI), and histo¬pathological investigations were used to assess in vivo immunomodulatory efficacy. Results: The body weight changes of the experimental animals were considerably greater at 100 mg/kg bw than at a higher dose (200 mg/kg bw). There was a substantial improvement of relative organ weights of the thymus and spleen at the low dose, but no effect on kidney weights was evi¬dent. The liver weight increased significantly (p < 0.05) at both doses. Total neutrophil, leukocyte, and lymphocyte counts, hemoglobin percentage, delayed hypersensitivity reaction, and PI were all significantly (p < 0.05) increased in mice receiving the lower dose. In contrast to the control group, the higher dose reduced immunological response, suggesting the negative influence of a higher dose of extracts on the immune reaction. Conclusions: The results demonstrate that orchid extracts can potentially modulate the innate immune system in the experimental animal. [J Adv Vet Anim Res 2021; 8(3.000): 479-488]